2008
DOI: 10.1194/jlr.m700258-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid transfer inhibitor protein (apolipoprotein F) concentration in normolipidemic and hyperlipidemic subjects

Abstract: Lipid transfer inhibitor protein (LTIP) is an important regulator of cholesteryl ester transfer protein function. We report the development of an immunoassay for LTIP and its use to quantify LTIP in plasma of varying lipid contents. A rabbit antibody against bacterially produced recombinant LTIP detected two LTIP isoforms in plasma differing in carbohydrate content. This antibody was used in a competitive, enzyme-linked immunoassay that uses partially purified LTIP bound to microtiter plates. To optimize LTIP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 23 publications
5
44
1
1
Order By: Relevance
“…in hypercholesterolemic subjects but reduced in some hypertriglyceridemic individuals (6,8). As an initial inquiry into a possible basis for these changes in LTIP levels, we investigated the response of hamster LTIP to diet-induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…in hypercholesterolemic subjects but reduced in some hypertriglyceridemic individuals (6,8). As an initial inquiry into a possible basis for these changes in LTIP levels, we investigated the response of hamster LTIP to diet-induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…To determine mRNA turnover, 1 mg/ml actinomycin D was added to cells following agonist treatment, and the decline in LTIP mRNA over time was determined. LTIP mass in conditioned cell media was determined by Western blot as previously described (6). Media was concentrated ?20-fold by cold acetone precipitation.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…This protein is also known as lipid transfer inhibitor protein which is able to inhibit CETP. Plasma apoF levels were found to be positively associated with HDL cholesterol in males but not in females (Morton et al 2008). The Rader group subsequently showed that overexpression of apoF in mice reduced HDL cholesterol levels by accelerating clearance from the circulation (Lagor et al 2009).…”
Section: Apolipoprotein Fmentioning
confidence: 97%